2013
DOI: 10.1242/jcs.125393
|View full text |Cite
|
Sign up to set email alerts
|

Sorting receptor SORLA – a trafficking path to avoid Alzheimer disease

Abstract: SummaryExcessive proteolytic breakdown of the amyloid precursor protein (APP) to neurotoxic amyloid b peptides (Ab) by secretases in the brain is a molecular cause of Alzheimer disease (AD). According to current concepts, the complex route whereby APP moves between the secretory compartment, the cell surface and endosomes to encounter the various secretases determines its processing fate. However, the molecular mechanisms that control the intracellular trafficking of APP in neurons and their contribution to AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 138 publications
(160 reference statements)
3
97
0
5
Order By: Relevance
“…Phosphorylation of SORLA in vivo was described before [16][17][18]. Our phosphorylation analysis further detected phosphorylation of synapsin 1 and 2 at the putative 14-3-3 binding sites (Ser666 and Ser546) in mouse cortex, a prerequisite for 14-3-3 binding to these sites (Fig.…”
Section: Sorla Interacts With Synapsin Via 14-3-3-adaptor Proteinssupporting
confidence: 72%
“…Phosphorylation of SORLA in vivo was described before [16][17][18]. Our phosphorylation analysis further detected phosphorylation of synapsin 1 and 2 at the putative 14-3-3 binding sites (Ser666 and Ser546) in mouse cortex, a prerequisite for 14-3-3 binding to these sites (Fig.…”
Section: Sorla Interacts With Synapsin Via 14-3-3-adaptor Proteinssupporting
confidence: 72%
“…Using SorLA-deficient mice, we have found that in the absence of SorLA, AD pathology is strongly accelerated, suggesting a proximal role of SorLA in AD (18,19) that has led to the current model in which SorLA protects against AD (20).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Thus, earlier work mainly focused on the neurobiology of these receptors uncovering their ability to sort a number of target proteins in control of neuronal cell death and survival. Neuronal ligands for VPS10P domain receptors include neurotrophins and their receptors, or the amyloid precursor protein and progranulin, etiologic agents in Alzheimer's disease and in frontotemporal lobar degeneration, respectively (reviewed in 2,3 ). However, VPS10P domain receptors are also expressed in peripheral tissues with relevance to cardiovascular and metabolic processes.…”
Section: The Complex Cell Biology Of Sorting Receptorsmentioning
confidence: 99%
“…The role of VPS10P domain receptors as causative agents in neurodegenerative diseases has long been appreciated (reviewed in 2,3 ), yet their genetic implication in cardiovascular and metabolic disturbances came as a surprise. Here, we will discuss recent studies that have substantiated the involvement of VPS10P domain receptors in disturbances of the cardiovascular system and the metabolism, including hypercholesterolemia, atherosclerosis, obesity, and diabetes.…”
Section: Introductionmentioning
confidence: 99%